Incidence and risk factors of adverse drug reactions in patients with coronavirus disease 2019: A pharmacovigilance experience utilizing an ADR trigger tool - Bashayer Alshehail; Zainab Al Jamea; Royes Chacko; Fawaz Alotaibi; Nadia Ismail; Dhafer Alshayban (Elsevier, 2022)
Background: Since the World Health Organization declared coronavirus disease (COVID-19) as a pandemic, most countries started treating their patients with various therapies. However, the data regarding their safety and effectiveness is still lacking. Objectives: We aimed to evaluate the adverse drug reactions (ADRs) incidence and their predisposing factors among COVID-19 patients. Methods: A retrospective observational study that was conducted at a tertiary academic hospital from March - June 2020. Patients were included if they were ≥ 18 years old, inpatient, had a reverse transcriptase-polymerase chain reaction (PCR) positive for COVID-19, and were treated with; (lopinavir-ritonavir, hydroxychloroquine, chloroquine, favipiravir, ribavirin, or interferon-ß) either as monotherapy or combination therapy for three days or longer. The data of eligible patients were retrieved from the electronic medical records. A standardized data collection form was designed to collect patient demographics, COVID-19 severity based on the Saudi Ministry of Health management protocols, antiviral therapies, duration of therapy, and length of stay (LOS). The ADRs were identified via conducting a comprehensive review using predefined triggers and were evaluated using Naranjo Score. Results: A total of 155 patients were included of which 123 (79.4%) were males. In our sample, the incidence proportion of ADRs per patient was 72.3%. A total of 287 ADRs were identified most of them were hepatic (n = 101, 35.2%), gastrointestinal (n = 59, 20.6%), hematological (n = 47, 16%), and endocrine (n = 45, 15%). Hydroxychloroquine was the most common drug associated with ADRs (n = 155). The length of stay (10 - 20 days) was the only statistically significant with the ADR incidence (p-value = 0.008; 95 %CI 1.216:3.568). Conclusions: The ADRs are prevalent among COVID-19 patients, which assure the importance of implementing active hospital-based pharmacovigilance systems.